Prior knowledge and social entrepreneurial venture creation - Balunywa, Waswa (Emerald publishing company, 2021)
Purpose – The purpose of this study is to examine the mediating role of novelty ecosystem in the relationship between prior knowledge and social entrepreneurial venture creation (SEVC) among community-based organizations (CBOs) in Uganda. Design/methodology/approach – The study is cross sectional and quantitative. Data were collected from CBO owner-managers. Mean, standard deviations, correlations and structural equation modeling were conducted to check the relationships among variables. Findings – Results show that both prior knowledge and novelty ecosystem are significantly associated with SEVC. Results further indicate that novelty ecosystem partially mediates the relationship between prior knowledge and SEVC. Research limitations/implications – The design was cross sectional in nature, thus limiting monitoring changes in knowledge and its effect on SEVC. The results should be interpreted as they are because there could be some endogeneity biases, which were not detected like measurement errors and failure to identify appropriate instruments. Originality/value – This study provides an initial empirical evidence on the relationship between prior knowledge, novelty ecosystem and SEVC using evidence from a developing African country – Uganda. Mostly, this provides an initial evidence of the mediation role of novelty ecosystem in the relationship between prior knowledge and SEVC.
: the mediating role of novelty ecosystem
Keywords: Prior knowledge; Novelty ecosystem; Social entrepreneurial venture creation; Uganda; CBO